The CO2 emissions in Finland, Norway and Sweden: a dynamic relationship - Agustin Alonso-Rodriguez (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
In this paper a dynamic relationship between the CO2 emissions in Finland, Norway and Sweden is presented. With the help of a VAR(2) model, and using the Granger terminology, it is shown that the emissions in Finland are affecting those in Norway and Sweden. Other aspects of this dynamic relationship are presented as well.
Keywords: 330; Paris 2015 Agreement; CO2 emissions; VAR models; Granger causality; impulse response functions; forecast error variance decomposition; software R MTS; RATS